Pengaruh Penerapan Alur Praktikum Merdeka Terhadap Peningkatan Kemandirian dan Keterampilan Praktikum Peserta Didik - Hartini, Hartini (Jurnal Didaktika Pendidikan Dasar, 2024)
This study aims to determine the effect of the implementation of the MERDEKA practical flow learning on the independence and practical skills of class VIII students of SMP Negeri 2 Banjarnegara. The study used a quasi-experimental method with a one group pretest posttest design. The subjects of the study were class VIII students with a sample of 28 students from class VIIIF. Data collection techniques for independence and practical skills used observation and performance tests. The implementation of the implementation of the independent practical flow was documented with journal notes on the learning process. Pretest data for independence and practical skills used data before the implementation of the MERDEKA practical flow and the posttest was taken at the end of the independent practical flow learning. The data obtained in the form of pretest and posttest scores were analyzed using the effect size (d) calculation. It can be concluded that the implementation of the MERDEKA practical flow learning has an effect on student independence with an effect size value of 2.39 or a very high influence category and the practical skills of class VIII students of 1.88 or a high influence category.